FACTORIAL DESIGN OPTIMIZATION OF URANIUM (VI) CLOUD POINT EXTRACTION WITH TRITON X-100/TWEEN-40/D2EHPA/ BMIMMESO4 - NOUR EDDINE DJEBBARI; AFAF AMARA; AMEL DIDI; MOHAMED A. DIDI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This work reports the Uranyl (UO22+) extraction from water by the Triton X-100 / Tween-40 / D2EHPA / BMIMMeSO4 by two aqueous phases or cloud point extraction (CPE). The procedure has been developed to extract uranium (VI) using a mixture of non-ionic surfactants: Triton X-100 and Tween-40 in different contexts, and a mixture of lipophilic chelating extracting agent D2EHPA/ BMIMMeSO4. Several parameters such as the concentrations of Triton X-100, Tween-40, and uranium (VI) metal ions, temperature, solution pH have been studied by the 33 factorial design method, in order to find the optimum conditions for uranium (VI) extraction. The optimal extraction of uranium (VI) by micelle-mediated extraction (CPE) procedure was obtained for pH= 3.0, Na2SO4 (% w/w) = 9.0 and [UO22+] = 5.50 mM. This system has research value and application in wastewater treatment.